Analysis of Traffic Noise Levels on the Jalan Adi Sucipto, Kubu Raya Regency - Forbes, Hendy Hansen; Said, Said; Kadarini, S. Nurlaily (Jurnal Teknik Sipil, 2025)
The 1.75% population growth in Kubu Raya Regency since 2020 has intensified transportation activities, leading to increased traffic noise along Adi Sucipto Road and negatively affecting community comfort and health. This study analyzes traffic noise levels, develops a predictive regression model using JASP, and proposes mitigation strategies. The research employed a quantitative method, with primary data collected through field observations on July 20"“22, 2024, from 06:00 to 21:00 WIB using CCTV. The data collected included traffic volume, average speed, density, and noise levels. Analysis was carried out using descriptive statistics and multiple linear regression. The results show that traffic volumes ranged from 201 to 911 vehicles per 10 minutes, average speeds ranged from 30.98 to 56.16 km/h, and traffic density ranged from 24 to 152 vehicles/km. Noise levels were recorded between 66.4 and 77.1 dB, exceeding the WHO threshold (